Indah Jubin Enterprise / Mohd Amzar Ariff Ahmad Zaim ... [et al.] - Ahmad Zaim, Mohd Amzar Ariff; Mhd Fadzil, Mohd Helmy; Ahmad Fauzy, Farahdilla; Salim, Mohamed Azhar (2003)
The name of our business is Indah Jubin Enterprise. This business is combination sales and services installation of tiles. We choose this business because now days construction sector especially housing are very good potential and future. As we know Kedah government has a vision to develop the state like Selangor, Johor and Penang. They have own strategy under their plan called Kedah Maju 2010 Plan. Under this plan Kubang Pasu district where Jitra and Darulaman town located are one of several area focus developed. According this situation, we choose to open our business at this area.